High-intensity interval training and cardiac rehabilitation: An integrative review of recent evidence (Research, Society and Development, 2025)
High-Intensity Interval Training (HIIT) has proven to be an effective strategy in cardiac rehabilitation, improving cardiorespiratory capacity (VO₂ peak) and endothelial function. Studies indicate that HIIT may outperform Moderate-Intensity Continuous Training (MICE) in the short term, but long-term benefits remain uncertain. Beyond aerobic improvements, HIIT contributes to reduced blood pressure, improved body composition, and increased adherence to rehabilitation programs due to its shorter training duration. However, individual responses to HIIT vary, influenced by factors such as age, comorbidities, and baseline fitness level. Despite its effectiveness, HIIT safety must be monitored, as there may be cardiovascular risks in high-risk patients. Analyzed studies suggest that combining HIIT with resistance training may optimize cardiac rehabilitation benefits by promoting greater muscle mass preservation and risk factor control. The variability in training response highlights the importance of individualized protocols and continued exercise to maintain achieved benefits. Further research is needed to determine the best application of HIIT in cardiac rehabilitation, considering its long-term effects and strategies to ensure patient adherence.